Crystal Phase-Dependence of Ru@TiO2 Catalysts on the Product Selectivity in the Aqueous Phase Hydrogenolysis of Furfuryl Alcohol - Thea Seventina Desiani Bodoi; Shauqi Aulia Rifwanda; Rodiansono Rodiansono; Atina Sabila Azzahra; Utami Irawati; Ferensa Oemry; Gagus Ketut Sunnardianto; Indri Badri Adilina; Takayoshi Hara (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The crystal phase-dependence of ruthenium supported on titania (Ru@TiO2) catalysts on the product selectivity in the aqueous phase hydrogenolysis of furfuryl alcohol (FFalc) was investigated. The supported ruthenium nanoparticles (RuNPs) catalysts on TiO2 with different phases, c.a. rutile (R), anatase (A), and brookite (B) were employed. The Ru@TiO2(R) catalysed the hydrogenation-rearrangement reaction of furan ring to afford cyclopentanone/cyclopentanol (CPO/CPL) as the main product. The presence of high surface acidity in Ru@TiO2(R) catalyst promoted the hydrogenation-rearrangement of furan ring leading to CPO/CPL as the main product as indicated by NH3-TPD and pyridine-ATR-IR results. In contrast, the Ru@TiO2(A) catalyst selectively hydrogenolysed the furan ring to produce 1,5-pentanediol (1,5-PeD). This high selectivity of 1,5-PeD over Ru@TiO2(A) catalyst may be affected by the high dispersion of Ru NPs on TiO2 facets as depicted by the high H2-uptake and small particle sizes. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).